The relationship between purchase decision and perceived quality in cooking category of household appliances - Mutlu, Safiye Özge (My University, 2019)
Bugünün hızlı gelişen ve teknolojik dünyasında, algılanan kalite hem pazarlama işdünyası hem de akademik dünya için önemli bir konu olmuştur. Markaların arkasındaki tüketicialgısını bilmek ve anlamak, tüketiciyi en doğru şekilde etki altına alabilmek için önemli birkonu haline gelmiştir. Bu çalışmanın amacı beyaz eşya sektöründeki pişirici ürün grubu cihazmarkaları arasındaki algılanan kaliteyi incelemektir. Geniş kapsamlı bir literatür taramasısonrası algılanan kalite kavramı tanımlanmış ve yedi farklı alt boyut sunulupkavramsallaştırılmıştır: müşteri hizmetleri iletişimi, marka iletişimi, performans, ürünüstünlükleri, ürün tasarımı, marka imajı ve garanti. İkincil veriyi toplama amacıyla çevrimiçianket ile 352 kişiden yanıt alınmıştır. Çıkan sonuçlara göre algılanan kalite boyutlarının markagüveni ve marka sadakatine olan etkisi keşfedilmiş ve farklı markaların tüketici grupları analizedilmiştir.

In today’s fast developing and technological world, perceived quality has become animportant topic for both marketing business and academic world. Knowing and understandingthe consumer perception about the brands has become an asset to influence the consumers inthe most effective way. This study aims to examine the perceived quality for cooking appliancesin the household appliances sector. After an extended literature review, perceived qualiy isdefined and seven core dimensions of perceived quality are proposed and conceptualized:customer service communication, brand communication, performance, productadvances/ superiority, product design, brand image and warranty. An online survey with 352people was conducted to collect the secondary data. According to the results, the impact ofperceived quality dimensions on brand trust and loyalty intention is explored and differentbrands’ consumer groups are analyzed.
Keywords: Algılanan kalite; beyaz eşya; brand loyalty; brand trust; Business; evaletleri Perceived quality; householdappliances; İşletme; marka güveni; marka sadakati; Marketing; Pazarlama; white goods